Fecal microbiota transplant – a new frontier in inflammatory bowel disease - Sunkara T; Rawla P; Ofosu A; Gaduputi V (Dove Medical Press, 2018)
Tagore Sunkara,1 Prashanth Rawla,2 Andrew Ofosu,1 Vinaya Gaduputi3 1Division of Gastroenterology and Hepatology, The Brooklyn Hospital Center, Mount Sinai Health System, New York, NY, USA; 2Department of Internal Medicine, Sovah Health, Martinsville, VA, USA; 3Division of Gastroenterology, SBH Health System, Bronx, NY, USA Abstract: Inflammatory bowel disease (IBD) is a chronic multifactorial disease that affects the gastrointestinal tract and results from an aberrant immune response toward luminal antigens in genetically susceptible people. Most of the current therapies for IBD focus on the management of the inflammation by using corticosteroids, immune modulators, and more recently, monoclonal antibodies (biological therapy). Although these therapies provide benefit in most cases, there are still a significant number of patients who do not respond or become refractory over time, suggesting the need for alternative therapeutic options. In the last decade, it has been recognized that “dysbiosis,” an imbalanced gut microbiota, is a key element in IBD suggesting microbiome-based therapies as an attractive approach. Recently, fecal microbiota transplant (FMT) has been successfully used for the treatment of Clostridium difficile infection, and it is now under investigation for the treatment of IBD. Clinical trials data are still poor but strongly support a future introduction of FMT in therapy to manage IBD microbiome. More studies are needed to assess the optimal route of administration and the frequency of FMT, the best matched donor for each patient as well as the risks associated with FMT in IBD. Keywords: fecal microbiota transplant, FMT, inflammatory bowel disease, IBD, microbiome, dysbiosis, ulcerative colitis, Crohn’s disease